2011
DOI: 10.1186/1477-7827-9-40
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and expression of bovine nucleoplasmin 2 (NPM2): a maternal effect gene regulated by miR-181a

Abstract: BackgroundNucleoplasmin 2 (NPM2) is an oocyte-specific nuclear protein essential for nuclear and nucleolar organization and early embryonic development. The aims of this study were to clone the bovine NPM2 gene, determine its temporal expression during oocyte development and early embryogenesis, and evaluate the potential role of miRNA-181a in regulation of its expression.MethodsA 329 bp cDNA fragment was amplified from bovine fetal ovary using primers designed based on the conserved regions of the human and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
50
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 39 publications
8
50
0
4
Order By: Relevance
“…The injection of NPM into the bovine oocyte after fertilisation results in a significant improvement in the rate of pregnancy (Betthauser et al 2006). This suggests that the role of NPM is extended to reprogramming the somatic nucleus (Lingenfelter et al 2011). Conversely, the common regulation system that down-regulates gene expression is associated with microRNAs (miRNA) and pre-microRNAs (miR).…”
Section: Molecular Markers Of Oocyte Developmental Competencementioning
confidence: 99%
“…The injection of NPM into the bovine oocyte after fertilisation results in a significant improvement in the rate of pregnancy (Betthauser et al 2006). This suggests that the role of NPM is extended to reprogramming the somatic nucleus (Lingenfelter et al 2011). Conversely, the common regulation system that down-regulates gene expression is associated with microRNAs (miRNA) and pre-microRNAs (miR).…”
Section: Molecular Markers Of Oocyte Developmental Competencementioning
confidence: 99%
“…The action of miRNAs on maternal mRNA degradation has been clear in Zebrafish embryos, which shows that the miR430 is abundant in the embryonic activation point, just at the moment the degradation of the maternal transcripts takes place (44) . Recent studies have shown that in the bovine, maternal mRNA as NOBOX and NPM2 are regulated under the action of the miR-181st and miR196a, respectively (104,105) . It is important to point out that the route of the degradation mediated by miRNAs is present only during the activation of the embryonic genome, and is absent during the oogenesis and in the initial stages of the embryo (47,52,54,106) .…”
Section: Maternal Effect On the Activation Of The Embryonic Genomementioning
confidence: 99%
“…La acción de miRNAs sobre la degradación de RNAm maternos ha quedado clara en embriones del Zebrafish, donde se observa que el miR430 es abundante en el punto de la activación embrionaria, justo en el momento en que sucede la degradación de los transcritos maternos (44) . Estudios recientes han demostrado que en el bovino, RNAm maternos como NOBOX y NPM2 son regulados bajo la acción de los miR-181a y miR196a, respectivamente (104,105) . Es importante señalar que la vía de degradación mediada por los of mice brg1-/-are arrested at the 2-4 cells stage (108) .…”
Section: Efecto Materno Sobre La Activación Del Genoma Embrionariounclassified
See 2 more Smart Citations